A Relationship of Monoamine Oxidase-A with Serotonin in Violent Antisocial Behavior in Iraqi Prisoners - Zaal, Ali Majeed; Saud , Asmaa Mohammed (Iraqi Journal of Science, 2024)
It is thought that the monoamine oxidase-A (MAOA) enzyme, which catalyzes key brain signaling chemicals like serotonin, noradrenaline, and dopamine, indirectly influences antisocial behavior by disrupting the neurotransmitter balance in brain regions and neural networks. This study aims to assess the MAOA enzyme level in serum and serotonin linked to antisocial behavior in cases in the prison of Baghdad City, Iraq. Blood samples were collected from (63) prisoners and (27) control groups, ages 18 years to 65 years, with a mean ± SD of 37.8 ± 8.8, all males, with different prison terms and different crimes for prisoners in the prison at Baghdad City, Iraq. MAOA and serotonin levels were measured in serum in prisoners and healthy men, and the results showed the serum levels of MAOA enzyme and serotonin were decreased in prisoners compared to the healthy (11.5 IU/ml vs. 19.5 IU/ml) and (79 IU/ml vs. 439 IU/ml), respectively, with the observed difference being significant (P < 0.001(. The results of the relationship between education and social violence were: illiterate 11.1%, primary school 27%, secondary 52.4%, and university 9.5%. The median serum level of MAOA and serotonin in the age group 18–39 years was (11.3 IU/ml, 68.3 ng/ml), respectively, and in the age group 40–65 years was (13 IU/ml, 139 ng/ml), respectively.